Evaluation of Yard Long Bean (Vigna unguiculata ssp. sesquipedalis) Genotypes for Commercial Production in the Central Mid hills Region of Nepal - Pandey, Suprabha; Shrestha, Surendra Lal; Gautam, Ishwori Prasad; Dhakal, Mira; Sapkota, Sangita (Nepalese Horticulture, 2020)
The experiment on evaluation of open pollinated genotypes of Yard long bean (Vigna unguiculata ssp. sesquipedalis) was conducted during summer season of 2016 and 2017 at Horticulture Research Division, Khumaltar Lalitpur to assess the variability in the genotypes and yield potentiality for commercial production. The experiment was laid out in Randomized Complete Block Design with three replications. Six genotypes viz. Great Wall 01, Great Wall 02, Great Wall 03, Great Wall 04 and Great Wall 08 were compared with Khumal Tane. Observations were recorded on fresh pod yield and yield attributing parameters. The plant vigor and plant uniformity score (1-5 scale) was not found significantly different among the tested genotypes. The highest number of pods per plant (46) was observed on the variety Great Wall 03 and the lowest number of pods (33) on Great Wall 01 followed by Khumal Tane (39). The fresh pod yield was noted the highest with Great wall 03 (24 t/ha) followed by Great Wall 2 (19.4 t/ha). The lowest yield was observed with Khumal Tane (12.7 t/ha). Likewise, Great Wall 03 was found tender whitish with green color when it matures and spongy type of fruit with mid early maturity (85-95 days) along with long harvesting period of 30-35 days. Although Great Wall 02 scored 4.7 in plant uniformity (1-5 scale) and 4.4 in plant vigor (1-5 scale) it was characterized as thick fleshy and whitish green color at maturity with smooth straight type flesh having early maturity (70-80 days) which could gain the demand of the market early compared to most popular Khumal Tane. Thus, among all genotypes Great Wall 03 and Great Wall 02 were recorded best for further evaluation and recommendation.